Tren Baru: Kinerja Unggul di Telkom Plasa Parepare Melalui Dinamika Rekrutmen dan Budaya Organisasi - Wahyudi, Wahyudi; A. Sapada, Achmad Faisal; Arifuddin, Arifuddin; Suwandi, Suwandi (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
The purpose of this study was to determine the Effect of Recruitment and Organizational Culture on Employee Performance at Telkom Plasa Parepare. The analytical method used is validity test, reliability test, multiple linear regression, partial test, simultaneous test and the coefficient of determination to determine the existing hypotheses in this study. The results showed that Recruitment (Xı) had no significant effect on Telkom Plasa Parepare Employee Performance (0.425 < 2.040) with a significant value (0.674 < 0.05) and Organizational Culture (X2) had a positive and significant effect on Telkom Plasa Parepare Employee Performance (2.977 > 2.040) with a significant value (0.006 < 0.05). Recruitment and Organizational Culture have a simultaneous effect on Telkom Plasa Parepare Employee Performance (7.522 > 3.30) with a significance (0.002 < 0.05).